NAVIGATING IDENTITY: STUDENTS’ CULTURAL JOURNEY IN ENGLISH WRITTEN COMMUNICATION - Wakerkwa, Dian Agustina Purwanto (STKIP Persada Khatulistiwa Sintang, 2024)
Language is a fundamental component of culture, facilitating the exchange of cultural knowledge and the formation of identity among cross-cultural users. This study investigates EFL students’ intercultural experiences and how these experiences are reflected in their writings as they attempt to negotiate and maintain their cultural identity. As a part of English language learning, producing written texts requires comprehension of linguistic traits entangled in culture. The success of foreign language learning has a greater chance when cultural considerations become integral to the learning process. Therefore, lecturers and students must recognize the inseparable relationship between language and culture and that culture is not limited to the ways it is expressed through words. The data were gathered from students’ argumentative essays on a culturally sensitive topic and analyzed using Ivani?’s identity framework, focusing mainly on the autobiographical and discoursal selves, supplemented by in-depth interviews. The findings indicate that despite diverse cultural experiences, all students expressed similar perspectives on the issue, aspiring to be recognized as individuals with a moral foundation inherent to their culture. Keywords: written discourse; cultural experience; culture; identity, EFL students